THE INFLUENCE OF COMPETENCE AND JOB PLACEMENT ON EMPLOYEE PERFORMANCE IN REGIONAL DEVELOPMENT PLANNING AGENCY - Barkah Ibnu Romadon; Wanta; Dwi Epty Hidayaty (PT. Berkah Digital Teknologi, 2024)
Purpose: The focus of this research is to determine how the competence and job placement of employees of the regional development planning agency in Karawang Regency affect their performance. Research Methodology: This study used a quantitative method and multiple linear regression analysis. The entire population of 56 employees was involved in this study. Results: The results showed that the competency variable had a partial significance of 0.03 on performance, while the work placement variable had a partial significance of 0.00. In addition, the competency and work placement variables together had a significance value of 0.00 on performance. Limitations: The study was limited to the Karawang Regency Regional Development Planning Agency, and the data was collected at a specific point in time. Contribution: This study provides insights into the importance of employee competence and job placement in improving employee performance within government agencies. The findings can help inform human resource management practices in the public sector.